Executive functions and mathematical competence in Chinese preschool children: A meta-analysis and review - Zhong, Zhiyong; Xu, Yongqi; Jin, Ruining; Ye, Chen; Zhang, Mengmeng; Zhang, Hao (Frontiers in Psychology, 2022)
Numerous studies have been conducted on the correlation between preschool children’s executive functions and mathematical competence, the findings of those studies are inconsistent. This study used meta-analysis to investigate the correlation between executive functions and mathematical competence of preschool children in China, and then explored the moderating effects of age, gender, and instruments. The researchers conducted an extensive search of CNKI, Web of Science, Google Scholar and used screening criteria to identify 22 studies of Chinese preschoolers aged 3–7 years from 2007 to 2021. The findings indicated that there was a positive correlation between Chinese preschool children’s executive functions and mathematical competence (r = 0496), of which the effect size between mathematical competence and inhibition control was 0.347, and the effect size for working memory was 0.432, with an effect size of 0.370 for cognitive flexibility. Furthermore, Moderation analysis suggests that the preschoolers’ age, gender, and instruments affected the association between the executive functions and mathematical competence. The implications of these findings for theory and practice deserve further discussion.